Strategies for the Development of Islamic Da'wah in Timpeh District Dharmasraya Regency - Afandi, Yusuf (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Â This study focuses on the strategy of developing Islamic da'wah in Timpeh District, Dharmasraya Regency. Timpeh sub-district is an area inhabited by a heterogeneous community because most of the people who occupy this area are transmigrants from various regions on the island of Java. The condition of this multicultural society makes da'wah more challenging than in areas where the community is homogeneous, so the right strategy is needed to develop da'wah in the Timpeh District so that it runs well. This study uses a qualitative descriptive method using data collected through in-depth interviews and non-participatory observations supported by a literature review. In-depth interviews were conducted with four resource persons who presented figures in the development of da'wah in the Timpeh District. This study found three strategies implemented in the development of Islamic da'wah in the Timpeh District, among others: increasing the competence of dai, mapping the potential of da'wah, and developing da'wah materials. These three strategies aim to increase the effectiveness of da'wah in the Timpeh District so that da'wah can be carried out correctly.Â Penelitian ini berfokus pada strategi pengembangan dakwah Islam di Kecamatan Timpeh Kabupaten Dharmasraya. Kecamatan Timpeh merupakan wilayah yang dihuni oleh masyarakat yang heterogen karena sebagian besar masyarakat yang menempati wilayah ini adalah para transmigran dari berbagai daerah di pulau Jawa. Kondisi masyarakat yang multikultural ini menjadikan dakwah lebih menantang dibandingkan di daerah yang masyarakatnya homogen, sehingga diperlukan strategi yang tepat untuk mengembangkan dakwah di Kecamatan Timpeh agar berjalan dengan baik. Penelitian ini menggunakan metode deskriptif kualitatif dengan menggunakan data yang dikumpulkan melalui wawancara mendalam dan observasi non partisipatif yang didukung dengan studi pustaka. Wawancara mendalam dilakukan dengan empat narasumber yang menghadirkan tokoh-tokoh dalam perkembangan dakwah di Kabupaten Timpeh. Penelitian ini menemukan tiga strategi yang diterapkan dalam pengembangan dakwah Islam di Kabupaten Timpeh, antara lain: peningkatan kompetensi dai, pemetaan potensi dakwah, dan pengembangan materi dakwah. Ketiga strategi tersebut bertujuan untuk meningkatkan efektivitas dakwah di Kecamatan Timpeh agar dakwah dapat dilaksanakan dengan benar.Kata Kunci: Dakwah Multikultural, Strategi Dakwah, Timpeh